Genistein Implications in Radiotherapy: Kill Two Birds with One Stone - Xiongxiong Liu; Tong Zheng; Yanyu Bao; Ping Li; Ting Zhao; Yan Liu; Hui Wang; Chao Sun (Molecules)
More than 70% of cancer patients receive radiotherapy during their treatment, with consequent various side effects on normal cells due to high ionizing radiation doses despite tumor shrinkage. To date, many radioprotectors and radiosensitizers have been investigated in preclinical studies, but their use has been hampered by the high toxicity to normal cells or poor tumor radiosensitization effects. Genistein is a naturally occurring isoflavone found in soy products. It selectively sensitizes tumor cells to radiation while protecting normal cells from radiation-induced damage, thus improving the efficacy of radiotherapy and consequent therapeutic outcomes while reducing adverse effects. Genistein protects normal cells by its potent antioxidant effect that reduces oxidative stress and mitigates radiation-induced apoptosis and inflammation. Conversely, genistein increases the radiosensitivity of tumor cells through specific mechanisms such as the inhibition of DNA repair, the arrest of the cell cycle in the G2/M phase, the generation of reactive oxygen species (ROS), and the modulation of apoptosis. These effects increase the cytotoxicity of radiation. Preclinical studies demonstrated genistein efficacy in various cancer models, such as breast, prostate, and lung cancer. Despite limited clinical studies, the existing evidence supports the potential of genistein in improving the therapeutic effect of radiotherapy. Future research should focus on dosage optimization and administration, the exploration of combination therapies, and long-term clinical trials to establish genistein benefits in clinical settings. Hence, the unique ability of genistein to improve the radiosensitivity of tumor cells while protecting normal cells could be a promising strategy to improve the efficacy and safety of radiotherapy.